2023
DOI: 10.3390/f14030462
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation in Leaf, Fruit and Seed Traits in Natural Populations of Eucommia ulmoides, a Relict Chinese Endemic Tree

Abstract: Eucommia ulmoides Oliver is a dioecious, pharmaceutically and economically important, and precious relict tree species endemic to China, and has been listed as a key protected tree species of national level II. Phenotypic variation in ten natural populations in some key traits is still obscure. In order to study the relationship between population variation in phenotypic traits and geoclimatic factors, 15 traits were analyzed in 117 female sampled tree from ten natural populations. The results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Similar results were reported for Eucommia ulmoides Oliv. [ 51 ] and Malania oleifera Chun and S.K. Lee [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported for Eucommia ulmoides Oliv. [ 51 ] and Malania oleifera Chun and S.K. Lee [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high genotypic variation in these traits indicated potential genetic variation among the 15 S. moorcroftiana accessions that could be used for selection and breeding ( Dong et al., 2019 ). Furthermore, these seed trait variation reflects the result of genetic variation and phenotypic plasticity in response to environmental variation ( Wang et al., 2023 ). This information helps to understand the response mechanism and variation rules of plants to the environment, which is important for the collection, preservation and evaluation of germplasm resources.…”
Section: Discussionmentioning
confidence: 99%
“…t/s is the variance component among populations, and σ 2 s is the variance component within the population (family) [27,29].…”
Section: Phenotypic Differentiation Coefficientmentioning
confidence: 99%
“…From long-term field observations, we found that E. angustifolia in Gansu Province has formed a rich resource diversity under a complex geography, climate, and long cultivation history, and different regions have significant phenotypic differences. Therefore, some reasons for the phenotypic diversity of E. angustifolia can be explained by exploring its phenotypic variation, so as to understand the response of E. angustifolia growth to the ecological environment and also provide some basis for the genetic improvement, diversity conservation, and resource management of E. angustifolia [27].…”
Section: Introductionmentioning
confidence: 99%